Role of Body Members in Constructing Metaphors in Persian Political Texts - Sharifi, Shahla; Pooresfahani, Ailin Firoozian; Pooresfahani, Aida Firoozian (Mediterranean Journal of Social Sciences, 2012)
The major aim of this study was to explore how the body parts play roles in Persian political texts as metaphorical expressionsaccording to cognitive point of view. Due to this fact, by examining a number of contemporary political expressions, the accumulateddata were attributed into different body members including: dast (hand), cheshm (eye), sar (head), pÄ(foot), ru (face), dahÄn (mouth), del(stomach, heart), shÄne (shoulder), angosht (finger), zabÄn (tongue), dandÄn (tooth), gush (ear), sine (breast), ghalb (heart) and gardan(neck). Based on the findings, there are fifteen body members by applying which the political metaphors are conceptualized andreflected in Persian political discourse. Furthermore, the results obtained from the current study revealed that among the human bodymembers which are conceptualized in Persian political texts, "head" is the most frequent one.